RELATON BETWEEN SHELL WEIGHT AND ECLOSION BEHAVIOUR IN TROPICAL TASAR COCOONS OF ANTHERAEA MYLITTA D. - MATHUR, S.K.; KARANDE, A.J.; CHOUDHARY, R.L.; RAO, P.R.T.; CHAKRAVORTY, D.; KHANNA, R.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Study on relation between higher shell weight and eclosion behaviour in Daba bivoltine tropical tasar cocoons of Antheraea mylitta D. indicated that 94.0% cocoons with higher shell weight (more than 2 g) emerged normally and only 5.5% cocoons remained unemerged. Out of emerged cocoons, 93.85% were female and 100% male. All emerged female moths copulated naturally successfully giving rise to 64.28% Dfls with average fecundity 220. This indicated that hgher shell weight had no adverse effect on eclosion and hence can be treated at par with normal cocoons with respect to production of Dfls.